Dopamine Appetite and Cognitive Impairment in Attention Deficit/Hyperactivity Disorder - Jonathan Williams; Eric Taylor (Neural Plasticity)
The underlying defects in ADHD (Attention Deficit/Hyperactivity Disorder) are not yet clear. The current paper tests three existing theories: State Regulation, Cognitive Deficit, and Temporal Difference (TD) learning. We present computational simulations of the Matching Familiar Figures Task and compare these with the experimental results reported by Sonuga- Barke (2002). The TD model contains four parameters: the learning rate, discounting for future rewards, brittleness (randomness) of behavior, and action bias. The results show that the basic TD model accounts well for control performance in trials of 5 sec, 10 sec, and 15 sec duration; but not for the deficits in ADHD performance at 5 sec and 15 sec. Extending the TD model to incorporate either a state regulation deficit, or working memory deficit and delay in starting trials, can provide a good account of both control and ADHD results, at all trial-lengths. We discuss the significance of the results for theories of ADHD and make suggestions for future experimentation.